Desenvolvimento e produção de bio-óleo a partir de resíduos lignocelulósicos - Zubiolo, Claudia (2015)
Vegetal biomass is a complex mixture and consists especially of cellulose, hemicellulose and lignin, structurally united. Its obtaining supplies agricultural and forest residues, and is of great importance as a source of renewable resources and of great interest across industries, especially agro-industries due to the production of millions of tons / year of waste. Bio-oil is a product derived from burning biomass at high temperatures (pyrolysis). Within this context, the objective is to do a brief review on the development and production of bio-oil from lignocellulosic residues, fitting to point out that in addition to production of biofuels such as bio-oil, biomass can also be economical source several other valuable products such as food additives, flavorings, fertilizers and agrochemicals. It is therefore of great importance that research be conducted to better use of waste generated, especially those not yet availed by industrial and agro-industrial sectors.